Detecting the adherence of driving rules in an energy-efficient, safe and adaptive driving system. (1st April 2016) - Yay, Emre; Martínez Madrid, Natividad; Ortega Ramírez, Juan Antonio
Highlights: A rule matching algorithm that matches driving rules against a driving behavior is proposed. Development of the rule matching algorithm in an energy-efficient, safe and adaptive driving system. Evaluation of the rule matching algorithm using 15 journeys and three driving rules. Results show a higher performance than existing algorithms. Abstract: An adaptive and rule-based driving system is being developed that tries to improve the driving behavior in terms of the energy-efficiency and safety by giving recommendations. Therefore, the driving system has to monitor the adherence of driving rules by matching the rules to the driving behavior. However, existing rule matching algorithms are not sufficient, as the data within a driving system is changing frequently. In this paper a rule matching algorithm is introduced that is able to handle frequently changing data within the context of the driving system. 15 journeys were used to evaluate the performance of the rule matching algorithms. The results showed that the introduced algorithm outperforms existing algorithms in the context of the driving system. Thus, the introduced algorithm is suited for matching frequently changing data against rules with a higher performance, why it will be used in the driving system for the detection of broken energy-efficiency or safety-relevant driving rules.